GaN Nuclear Batteries: Radiation Modeling for the Accelerated Contact Exposure of Betavoltaics. (2020) - Hubbard, Lance; Cowles, Christian; Prichard, Andrew; Sevigny, Gary; Johns, Jesse; Morales, Duriem Calderin; Kovarik, Libor; Fuller, Erin; Matthews, Bethany; Schwellenbach, David
Abstract: Betavoltaics (BV) cells (or nuclear batteries) have long-lasting power and high volumetric energy densities that open a broad range of applications that are not currently available, especially in low-power electronics for the internet-of-things, internal medical devices, and harsh environments. The introduction of very low-power electronics has opened up a market for the wide and accepted use of BV cells. As BVs have potentially decades-long useful lifetimes and are anticipated to be used in harsh environments, a method to describe accelerated contact aging has been developed. Monte Carlo radiation simulations show that energy can be deposited in the interface 10-50 times faster than real-world applications. The models can be used to design contact aging experiments for BV cell deployments.